Derivation and evaluation of Landsat-derived annual aboveground biomass maps for Arctic and Boreal North America, 1984-2022 - Wanwan Liang; Olivier van Lier; Mark A. Friedl; James T. Randerson; Brendan M. Rogers; Arden Burrell; Kai-Ting Hu; Piotr Tompalski; Matthew J. Macander; Daryl Yang; Douglas C. Morton; Eric Bullock; et al. (Remote Sensing of Environment, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Leveraging additional VIIRS information to improve wildfire tracking in the western US - Shane R. Coffield; Tempest D. McCabe; Wilfrid Schroeder; Yang Chen; Rebecca C. Scholten; Elijah Orland; Tianjia Liu; Elizabeth Wiggins; James T. Randerson; Melanie Follette-Cook; Douglas C. Morton (Remote Sensing of Environment, 2026)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (II) optimizing acquisition configurations - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Omar Regaieg; Zhijun Zhen; Rongjun Qin; et al. (Remote Sensing of Environment, 2023)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (I) methods and comparisons with actual data - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Douglas C. Morton; Omar Regaieg; Zhijun Zhen; et al. (Remote Sensing of Environment, 2023)

Cyclical prey shortages for a marine polar predator driven by the interaction of climate change and natural climate variability - Amanda C. Lohmann; Joseph P. Morton; Oscar M. Schofield; Douglas P. Nowacek (Limnology and Oceanography, 2023)
Between 1992 and 2018, the breeding population of Adélie penguins around Anvers Island, Antarctica declined by 98%. In this region, natural climate variability drives five‐year cycling in marine phytoplankton productivity, leading to phase‐offset five‐year cycling in the size of the krill population. We demonstrate that the rate of change of the Adélie breeding population also shows five‐year cycling. We link this population response to cyclical krill scarcity, a phenomenon which appears to have arisen from the interaction between climate variability and climate change trends. Modeling suggests that, since at least 1980, natural climate variability has driven cycling in this marine system. However, anthropogenic climate change has shifted conditions so that fewer years in each cycle now prompt strong krill recruitment, triggering intervals of krill scarcity that result in drastic declines in Adélie penguins. Our results imply that climate change can amplify the impacts of natural climate oscillations across trophic levels, driving cycling across species and disrupting food webs. The findings indicate that climate variability plays an integral role in driving ecosystem dynamics under climate change.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Tracking the Rates and Mechanisms of Canopy Damage and Recovery Following Hurricane Maria Using Multitemporal Lidar Data - Veronika Leitold; Douglas C. Morton; Sebastián Martinuzzi; Ian Paynter; María Uriarte; Michael Keller; António Ferraz; Bruce D. Cook; Lawrence A. Corp; Grizelle González (Ecosystems, 2022)

The role of fire in global forest loss dynamics - Dave van Wees; Guido R. van der Werf; James T. Randerson; Niels Andela; Yang Chen; Douglas C. Morton (Global Change Biology, 2021)
Fires, among other forms of natural and anthropogenic disturbance, play a central role in regulating the location, composition and biomass of forests. Understanding the role of fire in global forest loss is crucial in constraining land‐use change emissions and the global carbon cycle. We analysed the relationship between forest loss and fire at 500 m resolution based on satellite‐derived data for the 2003–2018 period. Satellite fire data included burned area and active fire detections, to best account for large and small fires, respectively. We found that, on average, 38 ± 9% (± range) of global forest loss was associated with fire, and this fraction remained relatively stable throughout the study period. However, the fraction of fire‐related forest loss varied substantially on a regional basis, and showed statistically significant trends in key tropical forest areas. Decreases in the fraction of fire‐related forest loss were found where deforestation peaked early in our study period, including the Amazon and Indonesia while increases were found for tropical forests in Africa. The inclusion of active fire detections accounted for 41%, on average, of the total fire‐related forest loss, with larger contributions in small clearings in interior tropical forests and human‐dominated landscapes. Comparison to higher‐resolution fire data with resolutions of 375 and 20 m indicated that commission errors due to coarse resolution fire data largely balanced out omission errors due to missed small fire detections for regional to continental‐scale estimates of fire‐related forest loss. Besides an improved understanding of forest dynamics, these findings may help to refine and separate fire‐related and non‐fire‐related land‐use change emissions in forested ecosystems.

Thinner bark increases sensitivity of wetter Amazonian tropical forests to fire - Ann Carla Staver; Paulo M. Brando; Jos Barlow; Douglas C. Morton; C.E. Timothy Paine; Yadvinder Malhi; Alejandro Araujo Murakami; Jhon del Aguila Pasquel (Ecology Letters, 2020)
Understory fires represent an accelerating threat to Amazonian tropical forests and can, during drought, affect larger areas than deforestation itself. These fires kill trees at rates varying from 2 lost in Amazon understory fires between 2001 and 2010. Trait‐enabled global vegetation models that explicitly include variation in bark thickness are likely to improve the predictions of fire effects on carbon cycling in tropical forests.

Toward an integrated monitoring framework to assess the effects of tropical forest degradation and recovery on carbon stocks and biodiversity - Mercedes M. C. Bustamante; Iris Roitman; T. Mitchell Aide; Ane Alencar; Liana O. Anderson; Luiz Aragão; Gregory P. Asner; Jos Barlow; Erika Berenguer; Jeffrey Chambers; Marcos H. Costa; Thierry Fanin; et al. (Global Change Biology, 2016)
Tropical forests harbor a significant portion of global biodiversity and are a critical component of the climate system. Reducing deforestation and forest degradation contributes to global climate‐change mitigation efforts, yet emissions and removals from forest dynamics are still poorly quantified. We reviewed the main challenges to estimate changes in carbon stocks and biodiversity due to degradation and recovery of tropical forests, focusing on three main areas: (1) the combination of field surveys and remote sensing; (2) evaluation of biodiversity and carbon values under a unified strategy; and (3) research efforts needed to understand and quantify forest degradation and recovery. The improvement of models and estimates of changes of forest carbon can foster process‐oriented monitoring of forest dynamics, including different variables and using spatially explicit algorithms that account for regional and local differences, such as variation in climate, soil, nutrient content, topography, biodiversity, disturbance history, recovery pathways, and socioeconomic factors. Generating the data for these models requires affordable large‐scale remote‐sensing tools associated with a robust network of field plots that can generate spatially explicit information on a range of variables through time. By combining ecosystem models, multiscale remote sensing, and networks of field plots, we will be able to evaluate forest degradation and recovery and their interactions with biodiversity and carbon cycling. Improving monitoring strategies will allow a better understanding of the role of forest dynamics in climate‐change mitigation, adaptation, and carbon cycle feedbacks, thereby reducing uncertainties in models of the key processes in the carbon cycle, including their impacts on biodiversity, which are fundamental to support forest governance policies, such as Reducing Emissions from Deforestation and Forest Degradation.

Satellite‐based evidence for shrub and graminoid tundra expansion in northern Q uebec from 1986 to 2010 - kelly M. McManus; Douglas C. Morton; Jeffrey G. Masek; Dongdong Wang; Joseph O. Sexton; Jyoteshwar R. Nagol; Pascale Ropars; Stéphane Boudreau (Global Change Biology, 2012)
Global vegetation models predict rapid poleward migration of tundra and boreal forest vegetation in response to climate warming. Local plot and air‐photo studies have documented recent changes in high‐latitude vegetation composition and structure, consistent with warming trends. To bridge these two scales of inference, we analyzed a 24‐year (1986–2010) L andsat time series in a latitudinal transect across the boreal forest‐tundra biome boundary in northern Q uebec province, C anada. This region has experienced rapid warming during both winter and summer months during the last 40 years. Using a per‐pixel (30 m) trend analysis, 30% of the observable (cloud‐free) land area experienced a significant ( P N ormalized D ifference V egetation I ndex ( NDVI ). However, greening trends were not evenly split among cover types. Low shrub and graminoid tundra contributed preferentially to the greening trend, while forested areas were less likely to show significant trends in NDVI . These trends reflect increasing leaf area, rather than an increase in growing season length, because L andsat data were restricted to peak‐summer conditions. The average NDVI trend (0.007 yr −1 ) corresponds to a leaf‐area index ( LAI ) increase of ~0.6 based on the regional relationship between LAI and NDVI from the M oderate R esolution S pectroradiometer. Across the entire transect, the area‐averaged LAI increase was ~0.2 during 1986–2010. A higher area‐averaged LAI change (~0.3) within the shrub‐tundra portion of the transect represents a 20–60% relative increase in LAI during the last two decades. Our L andsat‐based analysis subdivides the overall high‐latitude greening trend into changes in peak‐summer greenness by cover type. Different responses within and among shrub, graminoid, and tree‐dominated cover types in this study indicate important fine‐scale heterogeneity in vegetation growth. Although our findings are consistent with community shifts in low‐biomass vegetation types over multi‐decadal time scales, the response in tundra and forest ecosystems to recent warming was not uniform.

Nitrogen deposition in tropical forests from savanna and deforestation fires - YANG CHEN; JAMES T. RANDERSON; GUIDO R. VAN DER WERF; DOUGLAS C. MORTON; MINGQUAN MU; PRASAD S. KASIBHATLA (Global Change Biology, 2010)
We used satellite‐derived estimates of global fire emissions and a chemical transport model to estimate atmospheric nitrogen (N) fluxes from savanna and deforestation fires in tropical ecosystems. N emissions and reactive N deposition led to a net transport of N equatorward, from savannas and areas undergoing deforestation to tropical forests. Deposition of fire‐emitted N in savannas was only 26% of emissions – indicating a net export from this biome. On average, net N loss from fires (the sum of emissions and deposition) was equivalent to approximately 22% of biological N fixation (BNF) in savannas (4.0 kg N ha −1 yr −1 ) and 38% of BNF in ecosystems at the deforestation frontier (9.3 kg N ha −1 yr −1 ). Net N gains from fires occurred in interior tropical forests at a rate equivalent to 3% of their BNF (0.8 kg N ha −1 yr −1 ). This percentage was highest for African tropical forests in the Congo Basin (15%; 3.4 kg N ha −1 yr −1 ) owing to equatorward transport from frequently burning savannas north and south of the basin. These results provide evidence for cross‐biome atmospheric fluxes of N that may help to sustain productivity in some tropical forest ecosystems on millennial timescales. Anthropogenic fires associated with slash and burn agriculture and deforestation in the southern part of the Amazon Basin and across Southeast Asia have substantially increased N deposition in these regions in recent decades and may contribute to increased rates of carbon accumulation in secondary forests and other N‐limited ecosystems.